'Egg-cased heart': a multimodality imaging approach to chronic constrictive pericarditis with egg-shell calcification: a case report. Issue 2 (15th February 2022) - Sane, Pratik Sudhir; Sankardas, Ajit Mullasari; Bhardwaj, Kambarnatham Srinivasan; Kurian, and Valikapathalil Mathew
Abstract: Background: Constrictive pericarditis (CP), also known as Pick's disease, is a sequela of chronic inflammation of the pericardium. Pericardial calcification is a common occurrence in CP; however, extensive egg-shell like calcification is rare. Our case, highlights, how a multi-modality imaging in a middle aged female helped to diagnose chronic constrictive pericarditis (CCP) with egg-shell like calcification encasing the heart. Case summary: Middle aged female with features of right heart failure, was diagnosed as CP based on two-dimensional echocardiography and cardiac catheterization. Computed tomography (CT) scan chest showed extensive egg-shell like calcification encasing the heart, suggestive of calcific CP. Subsequently, she underwent pericardiectomy, through median sternotomy approach and is currently on follow-up with asymptomatic cardiac status. Discussion: Extensive pericardial calcification encasing the heart like an egg-shell is rare in CCP. Likelihood of incomplete pericardial resection is high in calcific CP and hence a median sternotomy is preferred over anterolateral thoracotomy. A preoperative non-contrast CT scan defines the thickness, anatomic extent the calcification and its adherence to myocardium and surrounding structures. A reconstructed volume-rendered image delineates the extent of calcification precisely, thus determining the optimum surgical approach. A multi-modality imaging in CP, especially in calcific CP, is thus of paramount importance.